Role of average weight molecules content in the pathogenesis of the early period of isolated skeletal injury with blood loss complication - Mykolenko, A. Z. (Journal of Education, Health and Sport, 2017)
Mykolenko A. Z. Role of average weight molecules content in the pathogenesis of the early period of isolated skeletal injury with blood loss complication. Journal of Education, Health and Sport. 2016;6(11):760-766. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.288056 http://ojs.ukw.edu.pl/index.php/johs/article/view/4247 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. UDK 612.015-06:616.71-001-06:616-005.1]-092.9 ROLE OF AVERAGE WEIGHT MOLECULES CONTENT IN THE PATHOGENESIS OF THE EARLY PERIOD OF ISOLATED SKELETAL INJURY WITH BLOOD LOSS COMPLICATION A. Z. Mykolenko SHEI “Ternopil State Medical University by I. Ya. Horbachevsky Abstract Isolated skeletal injury (hip fracture) in the early period of traumatic disease accompanied by an increase of average weight molecules in blood level with a maximum of 3 days and normalization - after 7 days.Under these conditions, additional blood loss enhances the level of endogenous intoxication, accompanied by a significant accumulation in the blood fractions of average weight molecules, whose content after 7 days does not reach the level of control. Key words: isolated skeletal injury, blood loss, endotoxicosis.